Wasathiyyah Al-Sudais: Religious Moderation and Its Implementation in Indonesian Higher Education - Akhmad Alim; Mufid Mufid (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Amid the rising intolerance and radicalism among Indonesian university students, as evidenced by surveys from BNPT and PPIM UIN Jakarta, a significant gap exists in integrating authentic wasathiyyah religious moderation concepts into the Islamic Religious Education (PAI) curriculum. This issue is exacerbated by exposure to extremist narratives via social media and the lack of applicable models from contemporary scholars, necessitating a balanced theoretical foundation to foster moderate student character. Objective: This study aims to describe Abdur Rahman Al-Sudais's wasathiyyah concept from his work Bulugh al-Amal fi Tahqiqi al-Wasathiyyah wa al-Itidal and analyze its implementation at PTKIS such as STID Mohammad Natsir and STAI Al-Hidayah Bogor. Method: A qualitative descriptive approach was employed, utilizing library research, content analysis, observation, and interviews, focusing on Al-Sudais's primary text and field practices. Result: Key findings reveal tawassuth (middle path), itidal (justice), and tasamuh (tolerance) as the core of Al-Sudais's wasathiyyah, successfully applied through PAI curriculum integration, interfaith dialogue, and community service at both institutions. The discussion affirms that this model effectively counters right- and left-wing extremism, aligns with Kemenag RI policies, and contributes to national harmony in diversity through contextual and inclusive Islamic higher education. Conclusion: Al-Sudais's wasathiyyah framework provides a Qur'anically grounded, institutionally replicable model for religious moderation in Indonesian private PTKIs. Integrating this framework into PAI curricula, RMB activities, and community service programs demonstrably counters radical tendencies and aligns with Indonesia's RPJMN 2020–2024 moderation mainstreaming mandate.